A case study for teaching presence of community of inquiry in an asynchronous learning environment for preservice mathematics teachers - Ihlamur Türkoğlu, Begüm. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2023., 2023)
Online and blended learning-teaching practices and studies are increasing with technological developments. In these environments, building learning communities are important for effective learning experiences. Community of Inquiry (CoI) framework developed by Garrison, Anderson, and Archer (2000) explains meaningful online or blended learning experiences within the interaction of social, cognitive, and teaching presence. The purpose of this study is to explore the experiences of the pre-service mathematics teachers in the asynchronous components of a blended teacher education course on the teaching presence element of CoI. It is also aimed to understand teaching presence experiences of the teacher educator in this asynchronous environment to explore students’ experiences. An undergraduate blended course was selected as the focus of this case study. The data was collected through CoI survey and student interviews to explore teaching presence experiences of students. In addition, classroom observation notes, online discussions and postings, and interviews with the instructor were used as secondary data sources. Overall, the findings from CoI survey indicated that all presences of CoI yielded high perceptions in the course. The interview transcripts and secondary data sources show that teaching presence developed in the course and the experiences were parallel with the existing categories and indicators of CoI. On the other hand, the implications of teaching presence were unique to course activities and tools. There is a close interaction with the tools and teaching presence. Finally, the study found that there is a relationship between teaching presence and other presences.
Keywords: Mathematics teachers.; Educational technology.; Internet in education.